Evaluation of the quality of life of patients who use alcohol with harmful effects and have somatic complaints in primary medical care - Salden Вікторія (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the evaluation of the quality of life of patients who use alcohol with harmful effects and have somatic complaints in primary medical care.